The Effects of Massage Therapy after Decompression and Fusion Surgery of the Lumbar Spine: a Case Study - Keller, RMT, BPHE, Glenda (International Journal of Therapeutic Massage & Bodywork, 2012)
Background: Spinal fusion and decompression surgery of the lumbar spine are common procedures for problems such as disc herniations. Various studies for postoperative interventions have been conducted; however, no massage therapy studies have been completed.Purpose: The objective of this study is to determine if massage therapy can beneficially treat pain and dysfunction associated with lumbar spinal decompression and fusion surgery.Participants: Client is a 47-year-old female who underwent spinal decompression and fusion surgery of L4/L5 due to chronic disc herniation symptoms.Research Design: The research design was a case study in a private clinic involving the applications of seven, 30-minute treatments conducted over eight weeks. Common Swedish massage and myofascial techniques were applied to the back, shoulders, posterior hips, and posterior legs. Outcomes were assessed using the following measures: VAS pain scale, Hamstring Length Test, Oswestry Disability Index, and the Roland-Morris Disability Questionnaire.Results: Hamstring length improved (in degrees of extension) from pretreatment measurements in the right leg of 40° and left leg 65° to post-treatment measurement at the final visit, when the results were right 50° and left 70°. The Oswestry Disability Index improved 14%, from 50% to 36% disability. Roland-Morris Disability decreased 1 point, from 3/24 to 2/24. The VAS pain score decreased by 2 points after most treatments, and for three of the seven treatments, client had a post-treatment score of 0/10.Conclusions: Massage for pain had short-term effects. Massage therapy seemed to lengthen the hamstrings bilaterally. Massage therapy does appear to have positive effects in the reduction of disability. This study is beneficial for understanding the relationship between massage therapy and clients who have undergone spinal decompression and fusion. Further research is warranted.